Students’ Attitudes in Writing Reflection on Microteaching Course: An Appraisal Analysis - Azzra, Kania Shiva; Hartati, Elysa (J-Lalite: Journal of English Studies, 2024)
This research aimed to determine the students' attitudes and ideology in writing reflections on microteaching courses at a university in Yogyakarta majoring in English language education. The students’ reflection writing was analyzed using Martin & White (2005) appraisal theory. Two written reflections of students who took the microteaching course were used as research data. The methodology used in this research was descriptive qualitative to investigate and understand character subjectively by evaluating how individuals or groups express attitudes, views or evaluation of existing situations. Student A data consisted of 199 attitudes in reflective writing and were dominated by positive evaluation. Based on each attitude system, it was dominated by positive satisfaction, positive capacity, and positive valuation. This study found that student A brought an optimistic ideology and self-efficacy to written reflections. Student B consists of 27 data and is dominated by negative evaluation. Each attitude system is dominated by negative security, negative capacity, and positive reaction. Based on student B study of ideology, the written reflection is progressive. This research contributed to the future teacher’s professional development, especially in seeing them through their language use in their reflection.